Pelatihan Penggunaan Quizziz sebagai Media Assessment Pembelajaran bagi Guru di SMK Pariwisata Imelda Medan - Humaizi Humaizi; R. Hamdani Harahap; Muhammad Yusuf (Jurnal Kabar Masyarakat, 2023)
One application that can be used to help teachers evaluate student learning is Quizizz. The partners involved in this service program are teachers at the Imelda Medan Tourism Vocational School whose knowledge about the use of Information Technology in providing learning evaluations to students is inadequate. This activity is located at the Imelda Medan Tourism Vocational School, East Medan sub-district, Medan City. This activity applies an in-house training method by providing information technology literacy training to support learning assessments to increase teachers' knowledge and skills regarding the creation, use and optimization of the use of Quizizz as a learning evaluation. This knowledge can be used in the learning process to make it more interesting and combined with conventional learning techniques. During the training, the service team provided materials and tutorials on using Quizizz. The results obtained from this activity were an increase in the skills and knowledge of teachers at Imelda Medan Tourism Vocational School regarding the use of information technology (Quizziz) in making learning assessments in support of the Merdeka Belajar program.